From Commander to Leader - Lesław WEŁYCZKO; Józef LEDZIANOWSKI (Communications of International Proceedings, 2020)
The article presents key aspects of the conditions that are crucial for commanders who also want to be leaders. The authors draw attention to three key determinants, without which it is difficult to say that a commander is also a leader. The article also points out that not every commander will be a leader at the same time, because it requires a great effort and work on themselves from those who want to feel like they are leaders and self-control of their actions. Therefore, the three most important determinants that have a key impact on the formation of a leader's personality and his or her competence in this area should be understood both by the projectors of educational processes in the army and by future and current commanding officers themselves.
Keywords: personality; competences; leadership; emotional intelligence; effective officers' personality; self-management; motivations; emotions; personal and professional profile of the graduate.